IMPROVING LEARNING MATHEMATICS QUALITY THROUGH COOVERATIVE MODEL-BASED CONTEXTUAL - Rosita Rosita (Daya Matematis: Jurnal Inovasi Pendidikan Matematika, 2013)
This research is the classroom Action Research (CAR) which aims to improve the quality of mathematics learning through contextual – based cooperative model. This research was conducted at a SDN Kompleks IKIP 1 Makassar. The subjects were students of class VB (second semester Academic Year 2009/2010). Students activities data, the ability of teachers to manage learning and teachers’ activity was obtained by using the observation sheet and for student learning outcomes data used achievement test. Results showed that (1) student activities at the First Cycle of exiting categories of students activities do not meet the ideal time, on the second and third cycle students activities have fulfilled the ideal time. (2) learning management on Cycle I was in hight enougt category, Cycle II was in the high category, and the Cycle III was at a very high category, so the ability of teachers to manage learning was as expected. (3) Cycle I, Cycle II some activites of teachers still are beyond tolerance time, the Cycle III has been reduced rather than Cycle I and Cycle II, the activity of teachers has increased  (4) study results on Cycle I have not finished from 49 students who have not completed as many as 27 or 55.10% with average learning 61.22, in Cycle II students who have not finished are as many as 20 atau 40.81% with an average of 63.83 learning outcomes in the category has not been completed, while in the Cycle III has reached the completeness with the number of students who have not completed 10 or 24.40%, while the numbers of students who completed was as many as 39 or 79.59%, with an average of 75.39 learning outcomes. Descriptive statistics show that every cycle analysis showed the changes which increased at every cycle